2019
DOI: 10.1055/a-1015-0157
|View full text |Cite
|
Sign up to set email alerts
|

The Fetal Posterior Fossa on Prenatal Ultrasound Imaging: Normal Longitudinal Development and Posterior Fossa Anomalies

Abstract: Fetal neurosonography and the assessment of the posterior fossa have gained in importance during the last 2 decades primarily due to the development of high-resolution ultrasound probes and the introduction of 3 D sonography. The anatomical development of the posterior fossa can be visualized well with the newest ultrasound technologies. This allows better knowledge of the anatomical structures and helps with understanding of the development of malformations of the posterior fossa. In this article the longitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 68 publications
0
9
0
1
Order By: Relevance
“…There are several studies in the literature investigating the relationship of abnormal fetal posterior fossa appearance with chromosomal anomaly between 11 and 14 gestational weeks 14,18–20,22,24 . In the current study, since invasive intervention was not offered to patients with isolated enlarged 4 th ventricle, the karyotype results of 6 cases (27.2%) could not be determined.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…There are several studies in the literature investigating the relationship of abnormal fetal posterior fossa appearance with chromosomal anomaly between 11 and 14 gestational weeks 14,18–20,22,24 . In the current study, since invasive intervention was not offered to patients with isolated enlarged 4 th ventricle, the karyotype results of 6 cases (27.2%) could not be determined.…”
Section: Discussionmentioning
confidence: 82%
“…Fong et al studied BS and BSOB measurements by observing the presence or absence of IT 21 . A recent article by Pertl 22 also reviews the longitudinal development of the posterior fossa structures.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, with this inspiration and everyone's further discussion and understanding of the structure of the posterior fossa, it was later also gradually applied to predict cystic deformities of the posterior fossa (including DWM, BPC, Joubert's syndrome, etc.) [14,17,18]. Martinez-Ten P et al [19] followed up 28 cases of non-visualized 4VCP found in the rst trimester, 12 of which had central nervous system abnormalitie including DWM, BPC, OSB, cephalocele, megacisterna magna,, and 20 of 28 cases associated with aneuploidy chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, because the fetal posterior fossa structure is not fully developed in the rst trimester, the most direct diagnosis of these anomalies cannot be made. Most studies have con rmed that in early pregnancy, soft indicators related to the posterior fossa can be used to indicate whether there may be abnormalities, so as to guide clinicians to carry out corresponding interventions [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Haratz (64) , en base a estos estudios, en una serie prospectiva de 384 fetos normales propone la valoración rápida del cuarto ventrículo por la relación entre diámetro latero-lateral y antero-posterior, denominándolo indice del cuarto ventrículo ( fourth ventricle índex -4VI), el cual es mayor de 1 en fetos normales, independiente de la edad gestacional (figura 6A). Por medio de esa evaluación se podría lograr la detección de patologías como el síndrome de Joubert, romboencefalosinapsis, hipoplasia pontocerebelar y malformaciones corticales de tipo adoquinado (65)(66)(67)(68)(69)(70) . conclusIón En la evaluación del cerebro fetal durante el tamizaje con ultrasonido, es factible examinar el complejo anterior, cuerpo calloso, cisura de Silvio y cuarto ventrículo (no es obligada su evaluación de acuerdo a las guías ISUOG).…”
Section: Visualización De La Cisura De Silviounclassified